2020
DOI: 10.3390/f11121293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glow-Discharge Plasma Treatment on Contact Angle and Micromorphology of Bamboo Green Surface

Abstract: The inner and outer surfaces of bamboo stems are usually removed prior to the manufacture of bamboo panels because the surfaces are hydrophobic and difficult to bond with glue. Hence, the recovery and utilization ratio of bamboo during processing is low. This study focused on using glow-discharge plasma to treat green bamboo surfaces to make them less hydrophobic. The effects of plasma treatment on green bamboo stems were examined using contact goniometry (wettability), non-contact confocal profilometry and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Crystallinity is an essential parameter due to its relation to the mechanical properties of bamboo [17]. The bamboo on the bamboo helmet before and after modification was separated and ground to powder with a 30-60 mesh particle size using a micro plant grinder.…”
Section: Xrdmentioning
confidence: 99%
“…Crystallinity is an essential parameter due to its relation to the mechanical properties of bamboo [17]. The bamboo on the bamboo helmet before and after modification was separated and ground to powder with a 30-60 mesh particle size using a micro plant grinder.…”
Section: Xrdmentioning
confidence: 99%
“…There are a few challenges in replacing wood with bamboo, especially the poor bonding performance limiting its applications. 9,10 In bamboo, the lack of transverse ray cells reduces the porosity in lateral tissue. It makes adhesive flow only through the pores in cell walls, limiting penetration of adhesion in bamboo, especially in the transverse direction.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few challenges in replacing wood with bamboo, especially the poor bonding performance limiting its applications 9,10 . In bamboo, the lack of transverse ray cells reduces the porosity in lateral tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Liese et al reported that the bamboo cortex contains epidermis and hypodermis, and the primary function of bamboo's cortex is to block water and protect the tissues (Liese et al 1998). Meanwhile, Wang et al found that the contact angle of the untreated bamboo surface was 114˚, indicating a hydrophobic surface (Wang et al 2020). Cui et al noted that the silica in the bamboo cortex forms a perfect bonding interface to cellulose fibers.…”
Section: Introductionmentioning
confidence: 99%